Frequency, Risk Factors, and Mortality for Diabetes Mellitus in 1 225 130 Cats Under Primary Veterinary Care in the United Kingdom in 2019 - Oliver Waite; Ruth Gostelow; Emma Wright; Rosanne E. Jepson; Dave C. Brodbelt; Dan G. O'Neill (Journal of Veterinary Internal Medicine)
ABSTRACT Background Diabetes mellitus (DM) is a common endocrinopathy in cats. General population epidemiology and mortality studies on DM are lacking. Objectives Describe the incidence, prevalence, risk factors, and mortality for DM in cats under primary veterinary care in the United Kingdom (UK). Animals Random sample of 1053 confirmed DM cases from 1 255 130 cats in VetCompass. Methods Retrospective cohort study with a nested case–control study. Period prevalence and incidence risk of DM for 2019 were calculated. Multivariable logistic regression modeling was used to identify risk factors for DM. Results Annual prevalence was 0.39% (95% confidence interval [CI]: 0.37–0.42). Incidence risk (2019) was 0.14% (95% CI, 0.13–0.16). Mean age and median adult body weight of incident cases diagnosed with DM was 11.8 ± 3.5 years (n = 371) and 5.9 kg (interquartile range: 4.6–7.1, n = 327). Odds of DM were increased in cats ≥ 9.0 years (odds ratio [OR]: 5.11, CI, 4.10–6.24) compared with cats 4.5–9.0 years. Burmese (OR: 2.07, CI, 1.29–3.31) and Burmillas (OR: 8.30, CI, 2.59–26.62) had increased odds, whereas Bengals (OR: 0.24, CI: 0.06–0.98) and Ragdolls (OR: 0.11, CI: 0.02–0.80) had decreased odds of DM compared with crossbreeds. Of 51.2% (192/375) cats dead within 3 years of diagnosis, 93.0% (176/192) were euthanized; 19.7% (35/178) were euthanized ≤ 3 days after diagnosis. Conclusions and Clinical Importance Almost 1/250 cats in the UK live with DM annually. Burmillas were predisposed to DM, and protection against DM was shown in Bengals and Ragdolls. Early mortality associated with DM diagnosis in cats is high.